Representation Of Communication Between Cultures And Moral Messages In Animation Film (Study Analysis Of Animation Film "Upin Ipin" In MNC TV) - R. S. Dewi (Jurnal Komunikasi Pembangunan, 2012)
Abstract Currently the film is much loved children one of whom is the animated film-Ipin Upin, the film is not only a favorite of children but also teenagers and adults. Animation is quite booming in Indonesia, evidenced by the many different types of merchandise available. Even well-Ipin Upin ringtune often heard from many people mobile phones. When compared to interest in watching the people of Indonesia from children to adults the interest and hobby watch television much higher than the interest in reading. Seeing this condition, the TV should present the impressions of quality, especially for moral education and ethics are packaged in films or entertainment for viewers, not least the kids like in the movies Upin Ipin. The film picked up the different cultures in Malaysia as Malay, China, India and Indonesia. Representation of children of different cultures that will be examined in this research. In particular how cross-cultural communication and the moral messages that exist in the animated film upin this. The research was a qualitative discourse analysis, more in particular is of critical discourse analysis (Critical Discourse Analysis / CDA), Fairclough Entman model, it is used to see the meaning contained behind the animated film. Fairclough divides discourse analysis in three dimensions: text, discourse practice and sociocultutal practice. There were several important findings in this study, can generally be described that in the animated film-Ipin Upin laden with moral messages are packaged in a diversity of cultural backgrounds in the community "village windfall.” Highlighting the attributes and traditions of the three major tribes in Malaysia (Malay, Chinese and Indian). Imply a unity and togetherness of the diversity of cultural / tribal in Malaysia. Keywords: animated films, the representation, the moral messages